Changes in the gut microbiota composition of healthy young volunteers after administration of Lacticaseibacillus rhamnosus LRa05: A placebo-controlled study - Gai, Zhonghui; Dong, Yao; Xu, Fei; Zhang, Junli; Yang, Yujiao; Wang, Yuwen (Frontiers in Nutrition, 2023)
The gut microbiota promotes gastrointestinal health in humans; however, the effect of probiotics on the gut microbiota of healthy adults has not been documented clearly. This placebo-controlled study was conducted to assess the effect of Lacticaseibacillus rhamnosus LRa05 supplementation on the gut microbiota of healthy adults. The subjects (N = 100) were randomized 1:1 to receive (1) maltodextrin (placebo, CTL group) and (2) maltodextrin + strain LRa05 (1 × 1010 colony-forming units/day, LRa05 group). The duration of the intervention was 4 weeks, and changes in the gut microbiota from before to after the intervention were investigated using 16S rRNA high-throughput sequencing. In terms of alpha diversity, no significant difference in the composition of the gut microbiota was found between the LRa05 and CTL groups. 16S rRNA sequencing analysis showed that the relative abundance of Lacticaseibacillus significantly increased after supplementation with LRa05. Furthermore, a decreasing trend in the abundance of Sellimonas and a significant decrease in the salmonella infection pathway were observed in the LRa05 group compared with the CTL group. These findings indicate the potential of LRa05 to colonize the human gut and reduce the abundance of harmful bacteria in the microbiota.